1994
DOI: 10.1038/jcbfm.1994.3
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Negative DC Deflections following Middle Cerebral Artery Occlusion and KCl-Induced Spreading Depression: Effect on Blood Flow, Tissue Oxygenation, and Electroencephalogram

Abstract: Summary: In the periphery of ischemic brain lesions, transient spreading depression-like direct current (DC) deflections occur that may be of pathophysiological im portance for determining the volume of the ischemic in farct. The effect of these deflections on cerebral blood flow, tissue oxygen tension, and electrophysiology was studied in rats submitted to intraluminal thread occlusion of the middle cerebral artery (MCA) and compared with the changes following potassium chloride (KCl)-induced spreading depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
131
0
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(147 citation statements)
references
References 45 publications
(30 reference statements)
12
131
0
4
Order By: Relevance
“…For example, PIDs in cats were often associated with waves of hypoperfusion; the authors observed that persistent depolarization caused a secondary regional CBF decrease in the periinfarct zone (Ohta et al, 2001). Others also occasionally observed episodic hypoperfusion during PIDs in rat cortex (Back et al, 1994). Using reflectance spectroscopy, transient, spreading episodes of increased NADH fluorescence were recorded within penumbra in cats, suggesting that PIDs reduce oxygen availability, possibly due to reduced CBF (Strong et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, PIDs in cats were often associated with waves of hypoperfusion; the authors observed that persistent depolarization caused a secondary regional CBF decrease in the periinfarct zone (Ohta et al, 2001). Others also occasionally observed episodic hypoperfusion during PIDs in rat cortex (Back et al, 1994). Using reflectance spectroscopy, transient, spreading episodes of increased NADH fluorescence were recorded within penumbra in cats, suggesting that PIDs reduce oxygen availability, possibly due to reduced CBF (Strong et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, indicator perfusion techniques lacked temporal resolution and, therefore, did not provide information about the dynamic CBF changes during the acute stage of focal ischemia (McColl et al, 2004;Selman et al, 1990). Similarly, episodic hypoperfusion was only occasionally observed during PIDs, probably owing to the lack of spatial resolution with laser Doppler flowmetry (Back et al, 1994;Iijima et al, 1992;Mies et al, 1994;Nallet et al, 2000;Ohta et al, 2001). In our study, we showed the adverse consequences of ischemic depolarizations on CBF using a novel real-time CBF imaging technique with high spatial and temporal resolution (12 mm/pixel, one image every 7.5 secs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SD or SD-like depolarizations occur in the ipsi lateral cortex after MCA occlusion in rats (Gill et al, 1992;Iijima et al, 1992;Nedergaard and Hansen, 1993;Bak et al, 1994;Dietrich et al, 1994), as measured electrophysiologically. The fre quency varies with experimental conditions such as the method of the vascular occlusion, craniectomy, electrode insertion, anesthesia, brain temperature, blood glucose level, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences are important because CSD is thought to be fundamental to the development of aura in migraine (Lauritzen, 1994), and PID to underly the expansion of the focal injury in stroke and head injury (Sramka et al 1977 ;Back et al 1994 ;Hossmann, 1996 ;Mayevsky et al 1996). CSD wave propagation is associated with an ion redistribution across cell membranes in the affected regions, with a net cellular potassium efflux and corresponding sodium, chloride and calcium influx (Nicholson & Kraig, 1981).…”
Section: mentioning
confidence: 99%